Unlock the lock-in! Balance of rights in relation to betterment and compensation in Poland - Magorzata Barbara Havel (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2016)
Many Polish cities are faced with a dilemma: to enact their local land-use plans and be exposed to the immediate financial consequences of their adoption, or to protect their budgets against these costs and give up control of the development of the cities. There are very broad compensation rights for value decline due to planning regulations and for areas designated in plans for public roads. At the same time, current planning system policies and instruments in Poland largely neglect how the costs of providing urban infrastructure and services are socialized and how the benefits of development processes are privatized. The use of value capture instruments is very limited. This paper discusses the distribution of rights and liabilities in relation to the two main sides of the property-values effect caused by land-use planning regulations and public works in Poland, in the background of the new planning system and property-rights approach adopted in the country. The article presents the current situation, initially explores a possible ways forward based on varied international experiences, discusses the institutional design of land markets, and indicates the need for planning by Law and property rights.
Keywords: O18; P25; R52; 330; Betterment and compensation; delineation of property rights; planning system; Poland